Outbreak of clonal complex 22 Panton–Valentine leucocidin-positive methicillin-resistant Staphylococcus aureus. Issue 5 (September 2017) - Garvey, Mark I.; Bradley, Craig W.; Holden, Kerry L.; Oppenheim, Beryl
Aims: We describe the investigation and control of a nosocomial outbreak of Sequence Type (ST) 22 MRSA containing the Panton–Valentine leucocidin (PVL) toxin in an acute multispecialty surgical ward at University Hospital Birmingham NHS Foundation Trust. Methods: A patient was classed as acquiring methicillin-resistant Staphylococcus aureus (MRSA) if they had a negative admission screen and then had MRSA isolated from a subsequent screen or clinical specimen. Spa typing and pulsed field gel electrophoresis (PFGE) was undertaken to confirm MRSA acquisitions. Findings: The Infection Prevention and Control Team were alerted to the possibility of an outbreak when two patients acquired MRSA while being on the same ward. In total, five patients were involved in the outbreak where four patients acquired the PVL-MRSA clone from an index patient due to inadequate infection control practice. Two patients who acquired the strain developed a bloodstream infection. Infection control measures included decolonisation of affected patients, screening of all patients on the ward, environmental sampling and enhanced cleaning. Discussion: Our study highlights the potential risk of spread and pathogenicity of this clone in the healthcare setting. Spa typing and PFGE assisted with confirmation of the outbreak and implementation of infection control measures. In outbreaks, microbiological typing should be undertaken as a matter of course as without specialist typing identification of the described outbreak would have been delayed.